TINJAUAN TERHADAP PERKAWINAN BAGITO DI DALAM SUKUPALABIDAN SUKU PELIANG SONI MENURUTHUKUM ADATPETALANGAN DI KELURAHAN KAYUARA KECAMATANKERUMUTAN - P, Mega Lestaria; Hasanah, Ulfia; Putra, Setia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Bagito marriages are still practiced despite the consequences. Manypeople who perform bagito marriages have lives that are not peaceful andsomething always happens in their family life. The people of Kayuara Villagebelieve that the life experienced by this bagito marriage is filled with manycalamities. The people of the Palabi tribe and the Paliang Soni tribe of KayuaraVillage strongly follow the existing traditional culture. Therefore, the indigenouspeople of Kayuara Village prohibit tribal marriages and Bagito marriages. butthe indigenous people say that it is better to do tribal marriages than Bagitomarriages which should not be allowed. The purpose of writing this thesis is first,to find out the role of Customary Law regulations in Bagito marriage accordingto Petalangan Custom. Second, to find out the settlement and sanctions in theevent of a Bagito marriage in the Kerumutan Subdistrict Village.This type of research is sociological legal research, which is researchconducted on the identification of laws and the effectiveness of laws that apply insociety. In this case, looking at the implementation of bagito marriage carried outby the people of the Kayuara village, the nature of the research is descriptive,which provides precise data about humans, circumstances and other symptoms.The results showed that the role of customary law regulations in bagitomarriage according to Petalangan customary law in Kayuara Village, KerumutanDistrict has an important role in marriage, including traditional norms thatinfluence the marriage process. Customary law regulations often regulateprocedures, conditions and norms of behavior during marriage. Settlements andsanctions are carried out in accordance with the customs and norms that apply inthe community. The Bagito marriage settlement process involves open discussionsbetween the families of both parties involved. Settlements are made with respectfor existing customs and traditions, and seek a mutual agreement that isacceptable to both parties.Keywords: Customary Law-Marriage-Ban-Bagito.